2011
DOI: 10.1590/s1807-59322011001200018
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TGF-β1 in the blood during fracture repair in an estrogen-deficient rat model

Abstract: OBJECTIVES:Previous studies have reported that osteoporosis due to estrogen deficiency influences fracture healing. Transforming growth factor (TGF-β) has been found to be involved in fracture healing via the regulation of the differentiation and activation of osteoblasts and osteoclasts. The current study aimed to determine the effects of estrogen on the expression of TGF-β1 during fracture healing in ovariectomized rats.METHODS:Thirty female Sprague-Dawley rats weighing 200–250 g were assigned to: (i) a sham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
3
16
2
Order By: Relevance
“…Our observation opposes the results of several studies that have reported TGF-β1 has a protective role against osteoporosis and aids bone healing (3-5, 7, 11, 22). However, there are several other studies consistent with our results.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our observation opposes the results of several studies that have reported TGF-β1 has a protective role against osteoporosis and aids bone healing (3-5, 7, 11, 22). However, there are several other studies consistent with our results.…”
Section: Discussioncontrasting
confidence: 99%
“…The transforming growth factor (TGF)-β molecules are a super family of cytokines, including TGF-β, bone morphogenetic proteins (BMPs) and activins, which regulate the growth and differentiation of osteoblasts and osteoclasts (5). The TGF-β1, TGF-β2 and TGF-β3 are closely related mammalian isoforms, with TGF-β1 being the most abundant isoform in the bone (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some metabolic changes, such as those that occur due to a lack of estrogen, immobilization, metabolic acidosis, hyperparathyroidism, and systemic and local inflammatory diseases, affect the osteoclast count and activity associated with bone turnover [13]. Prostaglandins, insulin-like growth factors (IGFs), interleukins (IL-1, IL-6, and IL-11), tumor necrosis factor (TNF), and several local factors in bone, such as transforming growth factor (TGF), also contribute to the regulation of bone formation and resorption [13,14]. …”
Section: Resultsmentioning
confidence: 99%
“…The P-6 MSCs were seeded either treated with alendronate (Ale, Sigma, St. Louis, MO) at 10 −10 -10 −6 M for 6 hours or cultured in osteogenic medium that contained alendronate. RNA was collected from the cultures at 6 hours, day 3, 7 and 14 to perform real-time reverse transcript PCR (RT-PCR) for genes encoding proteins in TGF-β1signaling pathway ( TGF -β 1, Smad2 and Smad3 ) and markers of osteoblast differentiation ( Runx2 ), maturation (osteocalcin, Bglap ) or mineralization (osteopontin, Opn ) [4244]. …”
Section: Methodsmentioning
confidence: 99%